The political effects of the Russian-Ukraine war on international trade - Jerry Akpomedaye; A. E. Orhero (Department of Accounting Universitas PGRI Yogyakarta, 2024)
The Russian-Ukrainian war, an unprecedented geopolitical event, has triggered profound and far-reaching consequences for international trade. This paper examines the political effects of the conflict on global trade, focusing on how political decisions, economic sanctions, and realignments among nations are reshaping trade flows and policies. This study adopted a historical and content analysis. It concerns an in-depth examination of the documented data, from which relevant materials were drawn. The data collected for this study were synthesized and analyzed using trend analysis techniques. This study revealed that the Russian-Ukrainian war had significant impacts on global trade flows, including disruptions to supply chains, rising commodity prices, changes in trade relationships, economic consequences for agricultural markets and food security, reorientation of global trade, international trade and sanctions, and energy market dynamics. This study found that sanctions reshape trade dynamics, reconfigure partnerships, drive the development of covert economies, and affect long-term global trade structures. The study also showed that the most significant impacts of long-term consequences of the Russian-Ukrainian war on international trade policies were the shift from globalization to regionalization, the rise of economic blocs and fragmentation, the impact on global supply chains and resource security, growth of alternative financial and payment systems, sanctions as a tool of foreign policy, challenges to multilateral trade governance and the emergence of resilience and self-sufficiency policies. This study concluded that the political effects of the Russian-Ukrainian war serve as a critical reminder of the intricate interplay between politics and trade.